INTERNALISASI METODE HAFALAN AL-QUR’AN DALAM TRADISI ṢALÂT TAQWIYAH AL-HIFZH (STUDI LIVING HADITS DI PONDOK PESANTREN USYAQIL QUR’AN TALANGSARI JEMBER) - Siti Nur Azizahtul Luthfiyah (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
Memorizing the Koran becomes a part that is not released from the guarding of Allah SWT towards the authenticity of the Qur'an. However, the method of memorizing the Koran did not receive special attention and priority in the authoritative texts of the Islamic religion even though at the same time the authoritative texts, - especially the hadith, explained a lot of small and trivial matters. But PP. Usyaqil Qur'an has one of the traditional rituals relating to memorizing the Qur'an, - which are not practiced by many memorizers of the Qur'an elsewhere. Furthermore, they rely on the tradition to the Prophet. To that end, the author will examine the traditional phenomenon ṣalat taqwiyah al-hifzh as one of the hadith phenomena which the community has lived (living hadith) in order to know the practice of the prayer tradition and to know their understanding of the foundation of the prayer. The phenomenology approach, interview method, and observation were chosen by the researcher to find out directly the implementation of the tradition based on the perspective of the research object.